IMPLEMENTASI PENDIDIKAN KARAKTER PEDULI LINGKUNGAN PADA PESERTA DIDIK KELAS IV SD NEGERI SIASEM 04 - Eka Kurniadi; Moh. Toharudin; Dedi Romli Triputra (Pusat Riset dan Inovasi Nasional, 2022)
Character education in elementary schools requires special attention to apply it in the lives of students in order to form a strong noble character foundation attitude, environmental problems often occur in Indonesia and the lack of environmental awareness by fourth grade students at SD Negeri Siasem 04, thus students can carry out any of the following: one character value, namely caring for the environment in daily life, in developing efforts to improve the surrounding environment. This study aims to describe the implementation of character education caring for the social and non-social environment, and various kinds of obstacles that exist in SD Negeri Siasem 04. Using qualitative research types. The primary data of the study were students, while the secondary data were the principal and teachers, as well as other supporting documents. The data collection techniques in this study used observation, interviews and documentation. The data obtained were analyzed by data reduction techniques, data display and drawing conclusions or verification. Test the validity of the data using triangulation techniques and sources. The results showed that 1) The implementation of environmental care character education in SD Negeri Siasem 04 was carried out through, a) Environmentally friendly school policies, b) Implementation of an environment-based curriculum, c) Participatory-based environmental activities, d) Management of environmentally friendly supporting facilities, 2) Obstacles in implementing environmental care character education at SD Negeri Siasem 04, namely, a) Not including Adiwiyata schools. Lack of awareness of students and lack of understanding of students about the vision, mission and goals of the school, b) The curriculum is not independent and students lack understanding of the environment c) Lack of awareness of school residents to protect the environment. d) Students lack awareness to buy healthy food and damaged supporting facilities.